PENGARUH SELF EFFICACY DAN GRIT TERHADAP KEMAMPUAN SELF REGULATED LEARNING PADA SISWA SMP DI MOJOKERTO - Fahluzi, Bahrul Amiq; Affandi, Ghozali Rusyid (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to determine the effect of self-efficacy and grit on self-regulated learning (SRL) abilities in 7th grade students of SMPN 2 Ngoro Mojokerto. The scope of this study focuses on internal factors that influence students' abilities to organize, monitor, and evaluate their learning process independently. The method used is quantitative research with a correlational approach. The research sample amounted to 228 students taken using a saturated sampling technique. The research instruments included the Self-Efficacy Questionnaire for Children (SEQ-C), the Grit Scale for Children and Adults (GSCA), and the Academic Self-Regulated Learning Questionnaire (ASLQ). Data analysis was carried out using multiple linear regression with the help of the SPSS 25 program. The results showed that self-efficacy and grit have a positive and significant effect on self-regulated learning. This means that the higher the level of self-confidence and perseverance of students, the better their ability to regulate the learning process independently.